Pengolahan Produk Berbahan Dasar Buah Pepaya Sebagai Upaya Pemberdayaan Ekonomi Masyarakat Pedesaan Di Desa Pulau Pule Kecamatan Air Batu Kabupaten Asahan - Lubis, Porkas Sojuangon; Abdullah, Ujang; Wardani, Widia; Syahfitri, Dini; Qohar, Fansuri Fadil; Sinaga, Riny Viri Insy (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
Pulau Pule Village in Asahan Regency has abundant papaya agricultural potential, yet its utilization remains limited to selling fresh fruit with low economic value. The main problems faced by the community are the lack of post-harvest processing skills and low digital marketing literacy. This community service activity aims to empower the village economy, specifically for the PKK and POKDARWIS groups, through the diversification of processed papaya products. The method used is Asset Based Community Development (ABCD) with a Community Based Research (CBR) approach. The stages of service include four key steps: Discovery (identifying potential), Dream (formulating visions), Design (technical training on processing and packaging), and Deliver (marketing implementation and business group formation). The results of the activity show a significant increase in the knowledge and skills of partners in processing papayas into creative products such as papaya floss, dried sweets, and papaya leaf chips. Furthermore, the formation of a community of processed papaya product traders has become a forum for collective economic strengthening. Marketing assistance through marketplaces and social media has also increased the product's reach beyond the village area. The conclusion of this service is that optimizing local potential through a touch of culinary innovation and strengthening community institutions is capable of transforming the rural economic structure toward independence. This program is expected to be sustainable and serve as a model for village potential-based empowerment in Air Batu District.